2023
DOI: 10.21203/rs.3.rs-2818822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and risk factors of urinary incontinence among women in Africa: a systematic review and meta-analysis

Abstract: Background Patients of urinary incontinence (UI), defined as an involuntary leakage of urine, mostly suffer in silence. African women with the condition usually feel embarrassed and may not readily seek help. In spite of this, there appears to be no recent systematic review that quantifies the prevalence and risk factors of UI. This study, therefore, synthesizes all studies that report the prevalence of UI and risk factors across African countries.Methods A systematic review and meta-analysis were conducted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Urinary incontinence refers to the condition where an individual cannot control the excretion of urine, leading to unintentional leakage [1,2] . Population-based studies have indicated that urinary incontinence is more prevalent in females than males, with approximately 10% of adult females suffering from urinary incontinence [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence refers to the condition where an individual cannot control the excretion of urine, leading to unintentional leakage [1,2] . Population-based studies have indicated that urinary incontinence is more prevalent in females than males, with approximately 10% of adult females suffering from urinary incontinence [3,4] .…”
Section: Introductionmentioning
confidence: 99%